52nd Aerospace Sciences Meeting 2014
DOI: 10.2514/6.2014-0414
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid feedback design for subsonic and transonic airfoils and wings

Abstract: A hybrid inverse/optimization method for subsonic/transonic airfoil and wing shape design is presented with application to a range of airfoil and wing cases, in preparation for the test cases defined for the Special Session of SciTech 2014. The method is hybrid in the sense that it combines the traditional inverse design technique with an optimization procedure that determines the optimum target pressure distribution. This paper emphasizes the first part, the development of SCID, the Surface Curvature Inverse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…The work here aims at establishing a robust approach to specifying the target pressure for the inverse design method, and thus improve upon the work reported in the previous SciTech paper (2). The enhanced SCID hybrid design will be demonstrated for both airfoil test cases and the induced drag minimization of rectangular wing.…”
Section: Optimization Discussion Group Test Casesmentioning
confidence: 99%
See 1 more Smart Citation
“…The work here aims at establishing a robust approach to specifying the target pressure for the inverse design method, and thus improve upon the work reported in the previous SciTech paper (2). The enhanced SCID hybrid design will be demonstrated for both airfoil test cases and the induced drag minimization of rectangular wing.…”
Section: Optimization Discussion Group Test Casesmentioning
confidence: 99%
“…ii shearing the surface segments to change the curvatures as Campbell did in CDISC (6) The first one has been discussed in our previous work (2) and it showed that it works well for airfoils. The second method is to shear the surface segment to change the curvature at a point, as Campbell did in his work (6).…”
Section: Solutions To Scementioning
confidence: 99%
“…Starting from the initial design x (0) , the coarsest model c1 is optimized to produce a first approximation of the high-fidelity model optimum, x (1) . The vector x (1) is used as a starting point to find the next approximation of the high-fidelity model optimum, x (2) , which is obtained by optimizing the next model, c2. The process continues until the optimum x (K) of the last low-fidelity model cK.…”
Section: Optimization Methodologymentioning
confidence: 99%
“…Single-and multi-point formulations are included with one or more constraints. The problems have been solved by several groups in academia and industry and the first set of works [1][2][3][4][5][6][7][8][9] was presented at the AIAA SciTech conference in 2014. where f(x) is the objective function, x is the design variable vector, gj(x) are the inequality constraints, M is the number of the inequality constraints, hk(x) are the equality constraints, N is the number of the equality constraints, and l and u are the design variables lower and upper bounds, respectively.…”
Section: Introductionmentioning
confidence: 99%